2020
DOI: 10.1007/s10803-020-04632-y
|View full text |Cite
|
Sign up to set email alerts
|

The Gap Between Cognition and Adaptive Behavior in Students with Autism Spectrum Disorder: Implications for Social Anxiety and the Moderating Effect of Autism Traits

Abstract: The gap between cognitive ability and adaptive behavior has been thought to enhance psychopathology among people with autism, particularly among those without intellectual disability. We examined this association by exploring the gap between cognitive understanding of social behavior and socially adaptive behavior, and its impact on social anxiety symptoms, obsessive-compulsive symptoms, and depressive symptoms, among 53 university students with autism (without intellectual disability). A higher cognition-soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 108 publications
(111 reference statements)
0
3
0
Order By: Relevance
“…Poor adaptive behavior in both conditions has been attributed to deficits in intellectual functioning (as measured by Intellectual Quotient -IQ). However, recent studies in ASD indicated that individuals without intellectual disabilities show poorer adaptive behavior to what would be expected for their cognitive ability level (Kanne et al, 2011;Kraper et al, 2017;McQuaid et al, 2021;Nyrenius & Billstedt, 2020;Pathak et al, 2019;Zukerman et al, 2021). What is more, problems in adaptive behavior in ASD individuals with average/high IQ persist throughout the development (McQuaid et al, 2021;Nyrenius & Billstedt, 2020;Pathak et al, 2019;Zukerman et al, 2021), suggesting that the low IQ does not suffice to explain the limitations in adaptive functioning.…”
mentioning
confidence: 99%
“…Poor adaptive behavior in both conditions has been attributed to deficits in intellectual functioning (as measured by Intellectual Quotient -IQ). However, recent studies in ASD indicated that individuals without intellectual disabilities show poorer adaptive behavior to what would be expected for their cognitive ability level (Kanne et al, 2011;Kraper et al, 2017;McQuaid et al, 2021;Nyrenius & Billstedt, 2020;Pathak et al, 2019;Zukerman et al, 2021). What is more, problems in adaptive behavior in ASD individuals with average/high IQ persist throughout the development (McQuaid et al, 2021;Nyrenius & Billstedt, 2020;Pathak et al, 2019;Zukerman et al, 2021), suggesting that the low IQ does not suffice to explain the limitations in adaptive functioning.…”
mentioning
confidence: 99%
“…Overestimating autistic children's adaptive behavior skills based on their IQ scores may cause caregivers and service providers to underestimate the supports that autistic children need (Alvares et al, 2020). In turn, this lack of support may lead to increased anxiety and depression (Zukerman et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, understanding the mechanisms and processes that connects autism and social anxiety spectra may help modify current treatments or develop novel interventions to enhance the quality of life of affected individuals. Moreover, since the comorbidity of ASD and SAD raises the likelihood of developing other clinical issues such anxiety and mood disorders, drug or alcohol abuse, having a lower quality of life [48,90], and a higher risk of suicide [91], the timely treatment of this early-onset problem has the potential to significantly lower the burden of psychiatric illness in later life and reduce the substantial burden of disability.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the combined presence of ASD and SAD may imply worse treatment outcomes compared to patients with only one condition [45][46][47][48], a better understanding of overlapping features between the two conditions, including patterns of association between specific clusters of symptoms, seems crucial. Shedding light on the connections between the spectra of autism and social anxiety in this context may help to change current prevention and diagnostic strategies, eventually opening the way to new treatment approaches that could improve the quality of life of those affected.…”
Section: Introductionmentioning
confidence: 99%